Characteristics of Rural Children Admitted to Pediatric Hospitals - Peltz, Alon (Pediatrics, 2016)
BACKGROUND AND OBJECTIVES: Delivering high-quality care to children living in rural areas can be challenging. Compared with nonrural children, rural children often experience worse health outcomes. We assessed characteristics and hospitalizations of rural children admitted to US children’s hospitals in 2012. METHODS: Retrospective cohort analysis of 672190 admissions between January 1, 2012, and December 31, 2012, to 41 children’s hospitals in the Pediatric Health Information System database. ZIP codes were used to assess the patients’ rurality (by using Rural-Urban Community Areas classification), residence in a Health Professional Shortage Area, and family income. Multivariable regression was used to compare patient characteristics and hospital utilization between rural and nonrural children. RESULTS: Rural children accounted for 12% of all admissions (n = 81 360) to the children’s hospitals. Compared with nonrural children, rural children lived farther from the hospital (median [interquartile range]: 68 [48–104] vs 12 [6–24] miles) and more often resided in low-income ZIP codes (53% vs 24%) and Health Professional Shortage Areas (20% vs 4%) (P < .001 for all). Rural children had a higher prevalence of complex chronic conditions (44% vs 37%; P < .001) and medical technology assistance (15% vs 12%; P < .001). In multivariable analysis, rural children experienced higher inpatient costs (mean: $8507 vs $7814; P < .001) and higher odds of 30-day readmission (odds ratio: 1.1; 95% confidence interval: 1.0–1.1; P < .001). CONCLUSIONS: Rural children hospitalized at children’s hospitals have high rates of medical complexity and often reside in low-income and medically underserved areas. Compared with nonrural children, rural children experience more expensive hospitalizations and more frequent readmissions.